NEUROMYOPATHIES IN THE CORRECTION OF ATTENTION DEFICIT DISORDER AND HYPERACTIVITY IN SCHOOLCHILDREN - Olga A. Jafarova; Elena N. Danilenko (Открытое образование (Москва), 2016)
The proposed correction procedure in educational technology for children suffering from attention deficit disorder with hyperactivity. The analysis of the correlation of the results of psychological testing of the properties of attention and the dynamics of EEG with the efficiency of the educational process.